Tingkat Kesejahteraan dan Indeks Kebahagiaan Karyawan Perbankan Karyawan Perbankan di Kota Malang dan Kota Jember - Theresia Oktavia (Trunojoyo University of Madura, 2019)
Economic growth is influenced by several factors such as welfare and happiness. The purpose of this study was to determine the level of welfare and happiness of banking employees in the city of Jember and the city of Malang. The research method used in this study is a quantitative descriptive method. The data collection method used is a questionnaire and literature study while the data analysis method used is two, namely welfare analysis and factor analysis. The results of this study are 100 employees in Malang City and Jember City which are classified as prosperous. Based on happiness index, the level of happiness of bank employee in Jember city is higher than the level of happiness of bank employee in Malang City. The value of the happiness index of bank employees in Jember city is 80,61 and the happiness index of bank employees in Malang City is 72,40.